PENGARUH INTERACTIVE CONTROL SYSTEM TERHADAP CUSTOMER-ORIENTED MEASURES MELALUI EMPLOYEE-ORIENTED MEASURES SEBAGAI VARIABEL INTERVENING - Mozes Yoshua Bizaliel Mainake; Saarce Elsye Hatane (Business Accounting Review, 2017)
This study aimed to examine the direct and significant affect of Interactive Control System to Emplopyee-Oriented Measures, Employee-Oriented Measures to Customer-Oriented Measures, and Interactive Control System to Customer-Oriented Measures in go public manufactures in Surabaya. This study also examined the indirect and asignificant influence of Interactive Control System to Customer-Oriented Measures through Employee-Oriented Measures as interening variable in go public manufactures in Surabaya. This study used a quantitative approach, and the data obtained by distributing questionnaires to go public manufactures in Surabaya and processed by using smartPLS software. This study showed that there was positive significant relationship of Interactive Control System to Employee-Oriented Measures; Employee-Oriented Measures to Customer-Oriented Measures; and Interactive Control System to Customer-Oriented Measures in go public manufactures in Surabaya. Employee-Oriented Measures was adequate to become as intervening variable between Interactive Control System and Customer-Oriented Measures because the direct relationship between Interactive Control System and Customer-Oriented Measures was smaller relationship than the indirect relationship.